Pemberdayaan UMKM Desa Singosaren Melalui Program Literasi Digital - Kurnianingtyas, Chandra Dewi (Jurnal Atma Inovasia, 2022)
Singosaren is a village whose potential is strong on human resources. It is proven by the high number of productive age rate and Micro, Small, and Medium enterprises (SMEs) rate as the society occupation. SMEs in Singosaren tend to rely on conventional way of business. It is caused by limited skills to use business digital platforms. In this pandemic and amidst digital era, SMEs potential of Singosaren needs to bewell-empowered. This measure could be implemented through digital literacy. Digital literacy focuses on technology education in masterng the skills to utilize social media ande-commerce maximally. Digital literacy’s objective is for the SMEs are not just producing digital business contents but to also analyze and use the features. The digital literacy contains of two programs which are digibook and digitalk. Digibook consists of practical guidebook in practicing the digital businesses through e-commerce and social media. Digitalk contains educational video consisted of tips in using Instagram in effective ways based on target market.